Successful reversal of sleep apnoea syndrome following treatment for acromegaly, confirmed by polygraphic studies. Issue 758 (December 1988) - Main, G.; Borsey, D. Q.; Newton, R. W.
Abstract : A patient with acromegaly was shown to have obstructive sleep apnoea by polygraphic recordings. Following successful hypophysectomy, further recordings demonstrated resolution of obstructive sleep apnoea.